Uniform Crime Reporting Program Data (United States): County-Level Detailed Arrest and Offense Data, 1989 ([Verlag nicht ermittelbar], 1992)
The files in this collection contain counts of arrests and offenses for Part 1 and Part 2 offenses: murder, rape, robbery, assault, burglary, larceny, auto theft, arson, forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew violations, and runaways. County populations are also reported.